Interactive Learning in Primary Schools: Development of ICT-Based Interactive PowerPoint Media on Types of Waste and Waste Management - Deni Mulyadi; Ghullam Hamdu (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to develop and evaluate ICT-based interactive PowerPoint media focused on the topic of types of waste and waste management for use in primary school learning. The purpose of the development was to provide teachers with effective instructional tools and to foster student engagement and understanding of environmental science content. The development process followed the 4D model: Define, Design, Develop, and Disseminate. The Define stage included a needs analysis through classroom observation and media usage evaluation. During the Design and Develop stages, an interactive PowerPoint was created, incorporating text, audio, video, and interactive quizzes. Expert validation was conducted involving four experts: a subject matter expert, instructional design expert, media communication expert, and an end-user (classroom teacher). Validation results indicated that the media was highly valid, with expert scores ranging from 86.67% to 90%. Student responses were also positive, with a satisfaction score of 86.66%, demonstrating high levels of interest and motivation during the learning process. The media successfully delivered educational content on classifying and managing waste in a visually appealing and accessible manner, allowing students to engage in independent learning with embedded navigation instructions. In conclusion, the developed ICT-based interactive PowerPoint media is considered valid and effective for elementary education and is recommended for broader classroom implementation to enhance environmental literacy and learning outcomes.